European Sexual Dis/Integration : An Agonistic Paradox of Legitimacy in a Contested Union - Breiding, Malte (Lund Political Studies, 2025)
This dissertation examines how the legitimacy of the European Union’s (EU) support for LGBTIQ equality should be assessed and asserted amid the far right’s promotion of a rival vision for European cooperation rooted in anti-gender politics. Drawing on agonistic and queer theory, the EU’s support for LGBTIQ equality is conceptualised as an effort to forge a European pro-LGBTIQ consensus, termed sexual integration. Sexual integration faces a paradox: when support for LGBTIQ equality is legitimised as an expression of the EU’s true nature, the far right responds by seeking to redefine what the Union is and should be. Sexual integration may thus function as a ‘constraining consensus’, entrenching polarisation between rival conceptions of the Union’s nature. The legitimacy of sexual integration is therefore ‘im-possible’: possible insofar as it rests on a dominant LGBTIQ-friendly conception of the Union, yet impossible because the EU can always be imagined otherwise. The dissertation addresses this paradox in three steps. First, Richard Bellamy’s and Kalypso Nicolaïdis’ normative political theories on the EU are deconstructed, showing the limits of grounding legitimacy in contested conceptions of the Union. Second, an agonistic conception of European sexual citizenship and an analytical framework termed Global Queer Agonism are proposed to capture the contested nature of the EU’s support for LGBTIQ equality. Third, these tools are applied through discourse analysis, demonstrating how the EU’s legitimation of sexual integration shapes far-right efforts to advance a rival anti-gender EU conception in internal and external relations. To unsettle this state of polarisation, a post-foundational conception of the EU as ‘transitive’ and ‘vulnerable’ is proposed, affirming support for LGBTIQ equality while acknowledging the Union’s contested nature. The dissertation argues, first, that normative political theory on the EU should assess the legitimacy of sexual integration by attending to the polarising effects of forging consensus on the EU’s nature, while reconceiving how an LGBTIQ-friendly Union can be understood, justified, and pursued in ways that disturb such political divides; and, second, that the EU should assert the legitimacy of its support for LGBTIQ equality by affirming liveable lives for all across the pro-LGBTIQ and anti-gender divide, rather than seeking to master the Union’s nature beyond contestation.
Keywords: Normative political theory; Agonism; Queer theory; European Union; Queer International Relations; LGBTIQ equality; Legitimacy; Postfunctionalism; Norm polarisation; Normativ politisk teori; Agonism; Queer-teori; Europeiska unionen; Queer Internationella Relationer; LGBTIQ-jämlikhet; Legitimitet; Postfunktionalism; Normpolarisering